Adaptive measurement rate setting method in block compressed sensing of images - Ran LI; Zong-liang GAN; UIZi-guan C; UMing-hu W; HUXiu-chang Z (Tongxin xuebao)
Traditional block compressed sensing (BCS) of images uses the same measurement rate to measure each block,but some blocking artifacts appear in the reconstructed image on accounting of varying spatial characteristics in an image.This problem can be effectively solved by adaptively setting different measurement rate for every block.However,these existing methods require original digital image at the collector,which cannot be realized by using practical compressive imaging (CI) devices.In order to overcome this shortage,an adaptive measurement rate setting method is proposed and it can be easily achieved though hardware equipments.This method uses the CS measurements acquired at the collector to estimate the sample variance of each block directly,and then adaptively sets measurement rate of each block in terms of their sample variances and realize rate control.Experimental results show that proposed method can obtain a better qual-ity of reconstructed image than non-adaptive scheme,but there is a gap between proposed method and the adaptive scheme using the true block sample variance since the sample variance estimated in the measurement domain has some deviations.